TRANSFORMASI CERPEN MADRE KARYA DEWI LESTARI KE FILM MADRE KARYA SUTRADARA BENI SETIAWAN: KAJIAN EKRANISASI - Efendi, Risi; Hayati, Yenni; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2017)
The purpose of this article (a) to describe story of episode cerpen Madre by Dewi Lestari (b) to describe story of episode film Madre director by Beni Setiawan, (c) to describe similar and different story of episode cerpen  with film Madre. The Data of this study were story of episode Madre by Dewi Lestari and film Madre director by Beni Setiawan. Analyzed technique do with ekranisasi theory. The findings of the study showed that the decrease story of episode cerpan Madre by Dewi Lestari in film Madre director by Beni Setiawan  become to 27 story of episode. Increase story of episode in film Madre  director by Beni Setiawan become to 56 story of episode. The same variation changes event, figure and background story of episode in n cerpen Madre created by Dewi Lestari  and film Madre director by Beni Setiawan become to 11 story of episode.Keywords: Ecranization, Dewi Lestari, Short story